Pengurusan Perkahwinan Masyarakat Cina Di Repok, Sarikei, Sarawak - Yong, Edna Li Jia. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research is a study on Chinese Marriage Management in Repok, Sarikei, Sarawak. This study was conducted to identify the marriage management methods of Chinese society in Repok, Sarikei, Sarawak and study the marriage customs and cultures of the Chinese society in Repok, Sarikei, Sarawak as well as study the impact of traditional customs and cultures changes of marriage to the Chinese society in Repok, Sarikei, Sarawak. This study was conducted by using qualitative method which was interviewed 2 informants who are experts in this field.